PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA SUMBER DAYA ALAM - Hariman Satria (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractIn ius constitutum of Natural Resources, the liability of corporate criminal, in any case, has been set in fve laws. First, fsheries and forestry law have similar formulation that corporations act as makers–undertakers are convicted. Second, plantation law, corporations act as makers –the corporations are convicted. Third, environmental law, corporations as makers –the corporation and the orderer are convicted. Fourth, mineral and coal mining law, corporations as makers –the board and the corporation are convicted. Indeed, there are inconsistencies in the regulation of corporate criminal liability in natural resources sector resulting in legal uncertainty.IntisariDalam ius constitutum SDA, paling tidak pertanggungjawaban pidana korporasi diatur oleh lima undangundang. Pertama UU perikanan dan kehutanan memiliki rumusan yang sama bahwa korporasi sebagai pembuat–pengurus dipidana. Kedua, UU perkebunan, korporasi sebagai pembuat–korporasi dipidana. Ketiga, UU lingkungan hidup, korporasi sebagai pembuat–korporasi dan orang yang memberi perintah dipidana. Keempat, UU minerba, korporasi sebagai pembuat–pengurus dan korporasi yang dipidana. Tegasnya ada inkonsistensi dalam pengaturan pertanggungjawaban pidana korporasi di sektor SDA sehingga menimbulkan ketidakpastian hukum.